EFFECTIVENESS OF HOME EXERCISE PROGRAM WITH MODIFIED ROOD’S APPROACH ON MUSCLE STRENGTH IN POST CEREBRAL HAEMORRHAGIC INDIVIDUALS OF ASSAM: A RANDOMIZED TRIAL (International Journal of Physiotherapy, 2019)
Background: Physical therapists are integral to the rehabilitation of patients of stroke, and home exercise program (HEP) prescription is a routine part of physical therapy care. Strength training is imperative in interventions for stroke patients. Various components of Rood’s Approach are effective in stroke rehabilitation, an aspect that has not been thoroughly explored as yet.Methods: A randomized controlled trial study was done at Gauhati Medical College & Hospital, Assam. The subjects were 236 hemorrhagic stroke patients who were randomly assigned into two groups. Both the groups were given a HEP consisting of routine physiotherapy exercises. Additionally, one group out of the two was also taught exercises based on the Rood’s approach, consisting of facilitation and inhibition techniques with the help of sensory stimulation and repetitive task-specific activity. The output was evaluated in terms of muscle strength using Manual Muscle Testing (MMT) after three months of intervention.Results: It was observed that HEP with Rood’s approach significantly improved (p